Subjectivities gained and lost in melancholic female eunuchs in Alice Walker's selected novels - Sedehi, Kamelia Talebian (2016)
According to Julia Kristeva, melancholic subject suffers from the sense of loss which results from the loss of mother. As a consequence of this loss, the melancholic subject is a stranger to language, isolates herself, and does not have any interest in actions or even life itself. However, in my study, I contend that the loss of mother is not the only reason for melancholia in the female characters, Celie, Tashi, Mem, and Magdalena in the Alice Walker novelsThe Color Purple, Possessing the Secret of Joy, TheThird Life of Grange Copeland, and By the Light of My Father‟s Smile, which were selected for this study. These female characters not only lost their mother or mother figures but also their sexuality has been oppressed, and they have been harassed; therefore, they are led to melancholia. These female characters do not have any knowledge about their bodies; therefore, they easily accept whatever old rituals and men impose on them. This condition of women lacking knowledge and the misrepresentation of female sexuality has been referred to by Germaine Greer as that of being a female eunuch. The purpose of my study was to focus on the reasons behind Celie, Tashi, Mem and Magdalena's melancholia, and the ways they attempt to heal it; either successfully or not. Therefore, I merge the concepts of Kristeva‘s melancholic subject and Greer‘s female eunuch to provide a new reading of melancholia for the selected female characters. Moreover, my thesis also explores Walker‘s selected novels in light of Kristeva‘s speaking subject to indicate how the use of language by the main selected female characters and other characters can make and unmake their subjectivity. Through the use of the language two of the female characters gained their subjectivity while the two others lost their subjectivity as the language is not powerful enough to indicate their needs and desires.